FAKTOR-FAKTOR PENDUKUNG YANG MEMPENGARUHI PARTISIPASI LANSIA DALAM POSYANDU LANSIA : LITERATURE REVIEW - Zikri Alhalawi; Ledy Ervita (Politeknik Karya Husada, 2024)
The increasing number of elderly in Indonesia requires more attention to health services, such as Posyandu Lansia to support the quality of life of the elderly optimally. This study aims to analyze the factors that influence the participation of the elderly in Posyandu Lansia activities. The study used a literature review method of 157 articles which were filtered into 10 relevant articles published between 2021–2024. The results of the analysis show that elderly participation is influenced by internal and external factors. Internal factors such as education, health conditions, motivation, trust, work, and attitudes. While external factors, such as family support, the role of Posyandu cadres, accessibility, and infrastructure. Family support has proven to be significant in encouraging the activeness of the elderly, especially through emotional, instrumental, and information support, which provides a sense of security and confidence to the elderly. However, the low level of participation is still influenced by the lack of program socialization, the distance of the Posyandu location, and the culture of the community that relies more on traditional medicine. The results of this study recommend the importance of improving health education for the elderly and their families, training for cadres, and optimizing Posyandu infrastructure to increase elderly participation.